Responses of glomus cells to hypoxia and acidosis are uncoupled, reciprocal and linked to ASIC3 expression: selectivity of chemosensory transduction - Lu, Yongjun (Blackwell Science Inc, 2013)
Carotid body glomus cells are the primary sites of chemotransduction of hypoxaemia and acidosis in peripheral arterial chemoreceptors. They exhibit pronounced morphological heterogeneity. A quantitative assessment of their functional capacity to differentiate between these two major chemical signals has remained undefined. We tested the hypothesis that there is a differential sensory transduction of hypoxia and acidosis at the level of glomus cells. We measured cytoplasmic Ca(2+) concentration in individual glomus cells, isolated in clusters from rat carotid bodies, in response to hypoxia ([Image: see text] mmHg) and to acidosis at pH 6.8. More than two-thirds (68%) were sensitive to both hypoxia and acidosis, 19% were exclusively sensitive to hypoxia and 13% exclusively sensitive to acidosis. Those sensitive to both revealed significant preferential sensitivity to either hypoxia or to acidosis. This uncoupling and reciprocity was recapitulated in a mouse model by altering the expression of the acid-sensing ion channel 3 (ASIC3) which we had identified earlier in glomus cells. Increased expression of ASIC3 in transgenic mice increased pH sensitivity while reducing cyanide sensitivity. Conversely, deletion of ASIC3 in the knockout mouse reduced pH sensitivity while the relative sensitivity to cyanide or to hypoxia was increased. In this work, we quantify functional differences among glomus cells and show reciprocal sensitivity to acidosis and hypoxia in most glomus cells. We speculate that this selective chemotransduction of glomus cells by either stimulus may result in the activation of different afferents that are preferentially more sensitive to either hypoxia or acidosis, and thus may evoke different and more specific autonomic adjustments to either stimulus.